Rancang Bangun Page Flipper Buku Otomatis Berbasis Mikrokontroler Atmega328p - I Nyoman Sukarma; I Nengah Suparta; I Ketut Darminta; I Wayan Jondra; I Kadek Aris Mahardika (Journal of Applied Mechanical Engineering and Green Technology, 2022)
Abstract: Technological developments also affect the progress and motivation to read the book. One technology developed in the field of electronics is an effort to increase interest in reading. With the tool Design Building Page Flipper Automatic Book Using Microcontroller ATmega328P then can make an alternative to open the book sheet. In addition, this tool is also appropriately utilized by people with special needs or have physical limitations (hand disability). With this tool can make it easier for someone to read a book because it is designed using an automated system. The automatic book page flipper tool uses an ATmega328P Microcontroller 4 servo motors where the servo motor 1 moves 100° to lower the lever on the drive wheel with a time delay of 1 second along with the operation of servo 2 which is marked by the movement of the wheel rotating 100° so that the book sheet or file is slightly attracted by the 1 second delay, then servo 3 moves which functions as a hold for the book or file sheet with a 100° movement, with a time delay of 1 second and servo 4 moves 180° as the thrower of the book sheet or file. And the sound sensor functions to give commands to the ATmega328P microcontroller which will later give orders to the ATmega 328P microcontroller which will later drive all the servo motors when getting commands.   Keywords: Microcontroller, sensor, servo motor